Analisis Sistem Pengawasan Hakim Dalam Mewujudkan Peradilan Yang Akuntabel - Arifin Tumuhulawa; Ferari D. Susilo; Ramdan Kasim (LPPM Universitas Bina Taruna Gorontalo, 2024)
This study aims to examine and analyze the system of supervision and supervision of judges to realize an accountable judiciary. Research Methods Based on the research focus, this type of research is classified as normative legal research. Normative legal research is